A preliminary study on predicting the prognosis of testicular torsion based on indocyanine green-guided near-infrared fluorescence imaging - Liu, Xiaomeng; Xu, Yi; Ren, Yuqian; Sun, Qing; Cui, Xiaomeng; Huang, Cheng; Bai, Dongsheng (Frontiers in Pediatrics, 2026)
BackgroundTesticular viability is the primary basis for selecting the surgical approach during orchiopexy for testicular torsion (TT); however, there is currently a lack of methods that can objectively assess testicular viability intraoperatively. The purpose of this study is to evaluate testicular viability and predict postoperative testicular outcomes using indocyanine green-guided near-infrared fluorescence (ICG-NIRF) imaging during surgery for TT.MethodsWe retrospectively reviewed pediatric patients treated for TT at our hospital between January 2024 and December 2024. Intraoperative ICG-NIRF imaging was used to assess testicular viability. Cases were classified into three types based on the testicular fluorescence patterns: Type A (extensive parenchymal fluorescence), Type B (fluorescence limited to the tunica vasculosa), and Type C (no fluorescence). Follow-up ultrasounds were performed at 1, 3, and 6 months postoperatively to record testicular volume and blood flow, and to calculate the testicular atrophy index (TAI).ResultsThis study enrolled a total of 19 pediatric patients. The cases were distributed as follows: 8 cases of Type A, 8 cases of Type B, and 3 cases of Type C. At the 6-month postoperative follow-up, Type A testes all showed normal blood flow signals on ultrasound, seven cases exhibited no atrophy, and one case had mild atrophy, the TAI [median (P25, P75)] was 4.75% (−0.72, 9.34). Among the 8 Type B testes, ultrasound showed normal blood flow signals in 1 case, reduced blood flow in 5 cases, and absent blood flow in 2 cases. All cases experienced severe atrophy, with a TAI [median (P25, P75)] of 86.95% (83.83, 97.31). Among the 3 Type C testes, ultrasound revealed reduced blood flow signals in 1 case and absent blood flow signals in 2 cases. All cases demonstrated severe atrophy, with a TAI [median (P25, P75)] of 88.15% (86.65, 90.56). There was a statistically significant difference in the TAI on comparison of Type B and Type C with Type A, respectively (p = 0.003 and p = 0.030).ConclusionThe application of ICG-NIRF imaging during surgical intervention for TT can effectively assess testicular viability and predict the prognosis of TT.